Preclinical evaluation of SMM‐189, a cannabinoid receptor 2‐specific inverse agonist. Issue 4 (6th July 2015) - Presley, Chaela; Abidi, Ammaar; Suryawanshi, Satyendra; Mustafa, Suni; Meibohm, Bernd; Moore, Bob M.
Abstract: Cannabinoid receptor 2 agonists and inverse agonists are emerging as new therapeutic options for a spectrum of autoimmune‐related disease. Of particular interest, is the ability of CB2 ligands to regulate microglia function in neurodegenerative diseases and traumatic brain injury. We have previously reported the receptor affinity of 3′, 5′‐dichloro‐2, 6‐dihydroxy‐biphenyl‐4‐yl)‐phenyl‐methanone (SMM‐189) and the characterization of the beneficial effects of SMM‐189 in the mouse model of mild traumatic brain injury. Herein, we report the further characterization of SMM‐189 as a potent and selective CB2 inverse agonist, which acts as a noncompetitive inhibitor of CP 55, 940. The ability of SMM‐189 to regulate microglial activation, in terms of chemokine expression and cell morphology, has been determined. Finally, we have determined that SMM‐189 possesses acceptable biopharmaceutical properties indicating that the triaryl class of CB2 inverse agonists are viable compounds for continued preclinical development for the treatment of neurodegenerative disorders and traumatic brain injury.